HUBUNGAN FAKTOR RISIKO DENGAN BERATNYA RETARDASI MENTAL PADA SISWA SLB C BANDUNG - Marcelia*, Siti Aminah*, Uni Gamayani* (NEURONA, 2010)
INTRODUCTION MENTAL RETARDATION MR CAUSES LACK OF HUMAN RESOURCES IN ALL OVER THE WORLD INCLUDING INDONESIA ESPECIALLY IN BANDUNG THE PREVENTION OF PREVENTABLE RISK FACTORS BECOME IMPORTANT BECAUSE MR IS NOT CURABLE THERES NOT SO MANY DATA ABOUT THESE RISK FACTORS IN BANDUNG AND ITS RELANTIONSHIP WITH THE SEVERITY OF MR